Allograft nephrectomy versus nonallograft nephrectomy after failed renal transplantation: a systematic review by updated meta‐analysis. (6th July 2021) - Gavriilidis, Paschalis; O'Callaghan, John Matthew; Hunter, James; Fernando, Tyrrel; Imray, Christopher; Roy, Deb
Summary: There is limited evidence regarding the impact of allograft nephrectomy (AN) on the long‐term outcome of subsequent kidney re‐transplantation compared with no prior allograft nephrectomy. The aim of the present study was to conduct a systematic review and meta‐analysis to estimate the accumulation of evidence over time. Primary outcomes were 5‐year graft and patient survival. Cochrane library, Google scholar, PubMed, Medline and Embase were systematically searched. Meta‐analysis was conducted using both fixed‐ and random‐effects models. Study quality was assessed in duplicate using the Newcastle‐Ottawa scale. Sixteen studies were included, with a total of 2256 patients. All included studies were retrospective and comparative. There was no significant difference in 5‐year graft survival (GS) [Hazard Ratio (HR) = 1.11, 95% Confidence Intervals (CI): 0.89, 1.38, P  = 0.37, I 2  = 10%) or in 5‐year patient survival (PS; HR = 0.70, 95% CI: 0.45, 1.10, P  = 0.12, I 2  = 0%]. Patients in the AN cohort were significantly younger than patients in the nonallograft nephrectomy (NAN) cohort by one year. Prior allograft nephrectomy was associated with a significantly higher risk of delayed graft function (DGF), acute rejection, primary nonfunction (PNF), per cent of panel reactive antibodies (% PRA) and allograft loss of the subsequent transplant. Although, DGF, % PRA, acute rejection and primary nonfunction rates were significantly higher in the AN cohort, allograft nephrectomy prior to re‐transplantation had no significant association with five‐year graft and patient survival. Abstract : Although, DGF, % PRA, acute rejection and primary nonfunction rates were significantly higher in the allograft nephrectomy (AN) cohort; (AN) prior to re‐transplantation had no significant association with five‐year graft and patient survival.